Tari Kreasi Jaranan Cilik: Stimulasi Motorik Kasar Anak Usia Dini dalam Proyek Penguatan Profil Pelajar Pancasila - Masruroh, Ummi (Widya Sundaram : Jurnal Pendidikan Seni Dan Budaya, 2025)
This research examines the influence of Jaranan Cilik Dance Creations on early childhood gross motor development, focusing on improving balance, agility, and flexibility and its contribution to implementing the Pancasila Student Profile Strengthening Project. This research explores how dance can stimulate children's gross motor skills and support character-building based on Pancasila values. The method used was descriptive qualitative with observation, interview, and documentation approaches. The data was analysed using an interactive analysis model, including data reduction, data presentation, and conclusion drawing. The research findings show that Jaranan Cilik Dance effectively improves children's gross motor skills and instills positive characteristics such as cooperation and discipline. The contribution of this paper is to introduce Jaranan Cilik Creation Dance as a method that integrates dance with gross motor development and early childhood character. The results of this study are important for enriching culture-based learning methods in early childhood education and contributing to holistic and value-based curriculum development.